Troubling practices of control: re-visiting Hannah Arendt's ideas of human action as praxis of the unpredictable - Kohlen, Helen (Nursing philosophy, 2015)
In this article, Hannah Arendt's concept of action will be used to problematize current transformations of the health care sector and examine some responses by ethicists in light of those transformations. The sphere of human interaction that should typify health care work is identified as an action of unpredictable praxis in contrast to controllable procedures and techniques which increasingly take place in the health care sector.